Long Non-coding RNA CCAT1 Acts as an Oncogene and Promotes Sunitinib Resistance in Renal Cell Carcinoma - Shan, Liping; Liu, Wei; Zhan, Yunhong (Frontiers in Oncology, 2020)
Although sunitinib contributes to prolonging the progression-free survival of metastatic renal cell carcinoma significantly, the universal presence of resistance limits the initial response rate and restricts durable responses. The mechanisms involved in sunitinib resistance vary and need further investigation. We found lncRNA colon cancer-associated transcript-1 (CCAT1) overexpressed in sunitinib resistant cells while declined in the parental cells. Moreover, lncRNA CCAT1 increased significantly in samples with resistance to sunitinib compared to those with responses to sunitinib. The reduction of CCAT1 suppressed cell growth and colony formation while triggered apoptosis. Inversely, the ectopic expression of c-Myc reversed the inhibition of cell growth and enhancement of apoptosis by the knockdown of CCAT1. We also verified that anti-apoptosis protein Bcl-2 and Mcl-1 decreased along with the deregulation of CCAT1, whereas the expression of Bcl-2 and Mcl-1 restored in cells that were transfected sh-CCAT1 and c-Myc simultaneously. Apart from the in vitro experiments, we demonstrated that knockdown of CCAT1 boosted response to sunitinib by performing sunitinib-resistant ACHN mouse models. Briefly, lncRNA CCAT1 conferred renal cell carcinoma resistance to sunitinib in a c-Myc-dependent manner, providing a novel target for improvement of sunitinib therapy.